Facade, New Custom House - Ghosh, Ayan (2023)
The New Custom House stands at the intersection of S Vallabhdas Road and R Kamani Road. It was designed in collaboration by John Begg and George Wittet and completed in 1913. However, with the outbreak of World War I in 1914, it was converted into a military hospital. The building was formally handed over to the Customs Department in 1922.